WAKAF PERKHIDMATAN: PERSPEKTIF FIQH DAN CADANGAN PELAKSANAAN : Service Waqf: Fiqh Perspectives and Recommendations on Implementation - Amir , Zubair; Mazri, Nur Mardia; Rosele, Muhammad Ikhlas; Abdullah, Luqman (Jurnal Syariah, 2024)
Waqf is one of the Islamic philanthropies that can help improve the socio-economics of a society through humanitarian services and waqf is not limited to assets. In developing waqf property, the issue of manpower and management costs is a challenge for managers because it involves large and continuous funds. There is a need to clarify the law of using cash waqf to finance the cost of human resources. The objective of this study is to clarify the necessity of service waqf as well as its application in the development of waqf property through jurisprudential debate. This study uses a qualitative method by gathering the views of jurists regarding cash waqf, waqf benefit, and permanent conditions on mawqūf. The data is then analyzed and appropriate views are presented taking into account the current situation in Malaysia. The findings of the study show that the appropriate service waqf implementation is through the contribution of benefits to the public by donating the service wage payment to a waqf body. Therefore, the contribution of the benefit is named a service waqf scheme which consest of a voluntary contribution of expertise to the community. This kind of implementation is permissible according to the majority of jurists who allowed cash waqf. In order to encourage the community to give waqf through this scheme, the wāqif can get an income tax deduction from the amount of labor wages that is waqf. In addition, the company can introduce a program in the form of volunteering to encourage the contribution of expert energy for free by branding it as a service waqf contribution.